Hubungan Antara Waktu Kerja dan Beban Kerja Fisik dengan Perasaan Kelelahan Pada Pekerja di Home Industry Tahu di Dukuh Janten - Tesha Dwi Ayu Anisyah; Julian Dwi Saptadi (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2020)
Background: Fatigue is a safety hazard in the workplace and can reduce work productivity. Fatigue that occurs continuously will become chronic fatigue. The feeling of fatigue experienced by sufferers can occur before doing work, during work and can occur after doing work in the afternoon. Fatigue occurs when the workload is 30-40% of work capacity and static work is carried out for a long time. Extending work time more than the ability to work long will be a tendency for fatigue. Any kind of work will be a burden for those who do it, whether it is a physical or mental workload. Method: This type of quantitative research using observational analytic method with cross sectional approach. The sampling technique using purposive sampling with a population of 114 workers and a sample of 60 workers. The instrument used is a questionnaire and pulse measurement using a stopwatch. Data analysis used univariate analysis and bivariate analysis using the chi-square test. Results: Research shows that the relationship between work time and feeling of fatigue is obtained p-value 0.040 (p <0.05), which means that there is a relationship between workforce and feeling tired. While the physical workload with feelings of fatigue obtained a p-value of 0.012 (p <0.05) which means that there is a relationship between physical workload and feeling tired. Conclusion: There is a relationship between work time and feeling tired, there is a relationship between physical workload and feeling tired.